KARAKTERISASI PREPARAT NANOPARTIKEL KAFEIN DARI EKSTRAK KOPI ROBUSTA MENGGUNAKAN PLGA DAN PVA - Rika Saputri; Muhammad Totong Kamaluddin; Theodorus Theodorus; Sonlimar Mangunsong (Universitas Hang Tuah, 2022)
Coffee is one of the beverages favored by the public. Coffee contains caffeine which is able to increase concentration and this ability takes place depending on the dose received by the body. The purpose of this study is to characterize caffeine nanoparticles polymerized PLGA and Pva.In the manufacture of caffeine nanoparticles using ingredients in the form of robusta coffee beans that have been dried and roasted which is then done the extraction process with digesti method, so that caffeine obtained. Then the caffeine that has been obtained is made into a formulation of polylytic nanoparticles PLGA and PVA. In the process of making nanoparticle formulations are used emulsion solvent evaporation method. The formulation of caffeine nanoparticles is characterized using PSA and the particle morphology is performed using TEM. The result of characterization using PSA obtained an average diameter of 173.8 nm, zeta potential -16.2 mV and PDI of 0.148.For morphology see spheric surface shape. So that caffeine from orbusta coffee beans can be prepared using PLGA and PVA polymers using emulsion solvent evaporation method.